Simulation of calculation of combat vehicle fuel efficiency by reducing vehicle weight using aluminum material - Jofim Yordaniel Napitupulu; Riri Murniati; Adhi Kusumadjati; Agung Hirawan; Mochamad Ibnu Alwan; Ramandasoavina Blanchard (FoundAE, 2024)
In the contemporary landscape, combat vehicles are tasked with meeting multifaceted demands, ranging from fortified defense capabilities to enhanced operational versatility and lethal efficacy. At the crux of these requirements lies the pivotal challenge of managing vehicular weight, a parameter that profoundly impacts endurance, agility, and speed. Extensive research endeavors have shed light on aluminum as a compelling solution to mitigate this weight burden while ensuring the requisite durability in combat vehicles. Through the utilization of MATLAB simulations, this study endeavors to elucidate the correlation between mass reduction and fuel efficiency, culminating in the creation of a comparative graph. The findings of this research make a significant contribution by demonstrating that a 15 percent reduction in vehicle mass, equivalent to 324 kilograms through the substitution of conventional materials with aluminum, yields substantial fuel savings amounting to 13.36 percent, or 1.3 liters. Such insights underscore the pivotal role of material selection in optimizing fuel efficiency in combat vehicle design